Husbands’ knowledge and involvement in sexual and reproductive health rights of women in Bahir Dar City, Northwest Ethiopia: a community-based study - Jemberie, Mekdes Mengesha; Zewdu, Meseret; Rade, Bayew Kelkay (Frontiers in Public Health, 2024)
Background Sexual and reproductive health rights (SRHRs) are integral elements of the rights of everyone to the highest attainable standard of physical and mental health, but they are the most underdeveloped and least understood sphere of rights, especially in Africa, including the country of Ethiopia. The implementation of women’s SRHRs is essential for achieving gender equality and promoting women’s rights. Husbands’ knowledge and involvement play a significant role in improving women’s practice of their SRHRs. However, there is limited information/data about the level of husbands’ knowledge and involvement in Northwest Ethiopia, including Bahir Dar City. Therefore, this study aimed to assess husbands’ knowledge, involvement, and factors influencing their involvement in women’s SRHRs. Methods Community-based cross-sectional study design was conducted from March 20 to April 5, 2023, in Bahir Dar City, Northwest Ethiopia, among 391 husbands. Multi-stage sampling and simple random sampling technique were applied to select kebeles and study participants, respectively. Participants were interviewed face-to-face using structured and pretested questionnaire. Binary logistic regression was applied to identify associated factors, and a p-value of <0.05 was a cutoff point to declare statistical significance. Results In this study, 50.6% (198/391) of the husbands had good knowledge about their wives’ SRHRs and 44.2% (173/391) (95% CI, 39.3–49.1%) of the husbands were involved when their wives practiced their SRHRs. Access training/education about sexual health [AOR = 5.99; 95% CI (2.7–13.2)], husbands’ advance educational level [AOR = 8.81; 95% CI (2.04–38)], good knowledge about SRHRs [AOR = 7.94; 95% CI (4.3–14.4)], low monthly income (<4,600 birr) [AOR = 9.25; 95% CI (4.2–20.5)], and had open discussion with family members and friends about SRHRs [AOR = 1.92; 95% CI (1.01–3.6)] were found to have significant association with husbands’ involvement. Conclusion Husbands’ level of knowledge on SRHRs of women and their involvement remain low. Therefore, responsible concerned bodies need to work on the strategies that help to improve men involvement and knowledge, and tackle the above-mentioned factors influencing their involvement.